Pemberdayaan Kader “Deras Ceria” Kader Cerdas Cegah ibu Hamil Anemia di Desa Glonggong - Kurniawati, Anik (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Abstract Introduction: The role of health cadres as part of the community element is an important factor in increasing social support from the community so that it can improve the quality of life of anemia clients in pregnant women. Cadres are expected to play an active role and be able to encourage, motivate and educate the community. Results of the National Health Indicator System (Siskernas) in 2016 The incidence of anemia in pregnant women in Indonesia is 37.1 (Indonesia, 2016). Based on a survey conducted, data was obtained from 24 pregnant women who attended pregnancy classes in Glonggong village, 13 pregnant women (54%) had Hb <11mg/dL. The community service program offered in the Glonggong Village Area, Gondang District, Sragen Regency is the Empowerment of Cadres "Deras Ceria" Smart Cadres to Prevent Anemia Pregnant Women Objective: 1. Increase cadre knowledge about anemia; 2. Improve cadre skills in filling out Fe monitoring cards in pregnant women Method: Empowerment activities are carried out by providing health education, lectures, discussions, questions and answers, and conducting direct practice on how to fill out Fe monitoring cards in pregnant women. A pretest and posttest were conducted on anemia in pregnant women. This activity was attended by 15 Posyandu/Health cadres representing Posyandu in Glonggong Village Result: There was an increase in cadre knowledge about anemia in pregnant women and an increase in cadre skills in using the Fe monitoring book for pregnant women. Conclusion: There was an increase in cadre knowledge about anemia in pregnant women and an increase in cadre skills in using the Fe monitoring book for pregnant women. Keywords: Anemia; Cadres; Knowledge